Block Implicit Hybrid One-Step Methods (Journal of Computational Mathematics, 1990)
A class of k-block implicit hybrid methods for solving the initial value problem for ordinary differential equations are studied, which take a block of k new values at each step. These methods are examined for the property of A-stability. It is shown that the method of order 2k+2 exists uniquely, and these methods are A-stable for block sizes k=1,2,3,4,5.